BILANGAN DOMINASI PERSEKITARAN PADA GRAF LENGKAP DAN GRAF BIPARTIT LENGKAP - Ratnasari, Lucia; Surarso, Bayu; Harjito, Harjito; Maunah, Uun (MATEMATIKA, 2017)
Given graph  with set of vertex  and set of edge E. Set  subset of  is called domination set if every point in  is adjacent with at least one point in  in graph . The minimum cardinality of all set of domination graph  is called domination number. Let  be a subset of , set  is called a neighborhood set if  with   induced subgraph  of . The minimum cardinality of all the neighborhood set of graph  is called the neighborhood number. There are several types of neighborhood domination number depending on the parameters. In this paper we examine the transversal neighborhood domination number and global neighborhood domination number in complete graph and complete bipartite graph.